Innovative contractual arrangement for land management of the commons - Rodrigues, Orlando (2018)
Today, there is growing recognition that land management needs to focus on the sustainable use of land and natural resources. Reducing the negative impact of the land use systems on the environment, economy and society is a central societal challenge. Often, in some peripheral or mountain regions, theoretically able to provide important environmental services, the regulatory framework of local communities or central states fails to shape resilient and sustainable land use systems (Blaikie and Brookfield, 2015). The urbanization of societies and the transformation of local communities, with loss of social regulation capacity, produced significant changes on land use systems. Consequently, the transformation of landscapes, produced by rural life styles evolution into urban like models, causes profound changes in the ecological functioning of the landscape and gradually results in a changing of spatial structure (Antrop, 2000). Progress in institutionalist’s research approaches has allowed a better comprehension of the structural components of many local resource use contexts (Healey, 2006). The extent of private decision-making is constrained by the formal legal framework, but also by informal institutional arrangements, with impact on property rights management. The capacity of the local communities to build effective institutional property rights management systems of the land is key issue on the persistence of resilient and sustainable natural resources use contexts (Penker, 2009). Property rights can be held at the individual or group level and, simultaneously, they might be protected at several extents, which allow a wide diversity of configurations. However, the persistence of effective land property rights management systems requires capable institutions to sustain their functionality. The problem often emerges because traditional institutions have not had the capacity to adapt themselves to global social systems change, particularly to demographic changes, and those regulatory systems collapsed. The challenge is how to define institutions that are more capable of responding to ecosystem dynamics and to social systems change. (Miranda, et alt 2006). In some cases, innovative community initiatives in sustainable land management, proved that are resilient solutions that can be managed by local communities. In this context is particular pertinent to analyze the different strategies that local communities develop to manage the common lands in this new context and also how they combine the common and private property land rights (Bromley et alt 1992, Tietenberg 2002). How to stimulate community initiatives in sustainable land management, it is a key issue (William et alt, 2016). In this work, we will discuss the findings from some case studies, which, combining collective use rights of the commons with an innovative contractual arrangement of private exploitation of some common lands, achieved a successful improvement of the community revenue, compared with other similar communities where the commons are in a semi-abandonment situation.